Parameter estimation and control design of solar maximum power point tracking - Hasan, Mashhood; Alhazmi, Waleed Hassan; Zakri, Waleed; Khan, Anwar Ulla (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Parameters evaluation, design, and intelligent control of the solar photovoltaic model are presented in this work. The parameters of zeta converters such as a rating of an inductor, capacitor, and switches for a particular load are evaluated its values to compare the trade of the existing model and promoted to research in the proposed area. The zeta converter is pulsed through intelligent controller-based maximum power point tracking (intelligent-MPPT). The intelligent controller is a fuzzy logic controller (FLC) which extracts maximum power from the solar panel using the zeta converter. The performance of evaluated parameters based on the solar system and zeta converter is seen by an intelligent control algorithm. Moreover, evaluated parameters of solar photovoltaic (PV) and zeta converter can be examined the performance of fuzzy based intelligent MPPT under transient and steady-state conditions with different solar insolation. The brushless direct current motor-based water pump is used as the direct control (DC) load of the proposed model. The proposed model can enhance the research and assist to develop a new configuration of the present system.